EVALUASI PELAKSANAAN PROGRAM FULL DAY SCHOOL TERHADAP PEMBENTUKAN KARAKTER PESERTA DIDIK - Rendi Setiya Kurniawan; Triana Rejekiningsih; Moh. Muchtarom (Asosiasi PPKn, 2019)
This research aims to identify: (1) The implementation of full day school program against students? character building in SMA Negeri 2 Karanganyar. (2) The evaluation of full day school program against students? character building in SMA Negeri 2 Karanganyar. (3) Obstacles and solutions in implementing full day school program against students? character building in SMA Negeri 2 Karanganyar. Descriptive method and qualitative approach are used in this research. Samples are taken by using purposive sampling method. Data are collected by doing interviews, observations, and document analysis. To gain data validity, this research uses data. Data are analyzed using interactive data analysis by following these steps: (1) Data collecting, (2) Data reduction, (3) Data presentation, and (4) Conclusion drawing or verification. Results show that: (1) The implementation of a ful day school program towards the formation of Students? character in SMA Negeri 2 Karanganyar is built through habituation, exemplary, and discipline training. (2) The evaluation of the CIPP (Context, Input, Process, Product) model in terms of context is good, because of the indicators of needs that have not been achieved the objectives to be achieved are in accordance with what is expected, namely to shape the character of learners, then environmental conditions are also very supportive and conducive. In terms of input shows that forexisting resources good enough it is known from existing facilities and infrastructure, the ability of the subject to support the program and strategy to achieve the program can be done well. In terms of the process to determine the extent to which the activities carried out in the program indicate that the indicators of program activities, ability to handle, utilization of facilities and infrastructure, and obstacles encountered by the school can do as expected. In terms of the product is the final evaluation that shows the results of the program carried out from the indicators of things done after the program runs can be done well, the impact obtained from the program can shape the character of students, and program excellence can shape the character of students (3) Obstacles that are met in this research are the following: First, students? basic character. Second, resources. Third, students? physical condition. Fourth, additional tasks from teachers. Solutions that come from this research are: always implementing the 5S policy [Senyum (smile), Sapa (greet), Salam (bow), Sopan (be polite), Santun (be kind)]and all assignments of teachers and students must be completed in school and live sincerely by referring to existing regulations.   Full Paper